2007
DOI: 10.1523/jneurosci.5399-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gamma and Alpha Activity during a Working Memory Task Engaging the Dorsal or Ventral Stream

Abstract: Despite extensive experimental work in both animals and humans, the actual role of oscillatory brain activity for working memory maintenance remains elusive. Gamma band activity (30 -100 Hz) has been hypothesized to reflect either the maintenance of neuronal representations or changing demands in attention. Regarding posterior alpha activity (8 -13 Hz), it is under debate whether it reflects functional inhibition or neuronal processing required for the task. The aim of the present study was to further elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
370
3
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(430 citation statements)
references
References 56 publications
45
370
3
6
Order By: Relevance
“…For the subjects of the WL+ group, the increase of alpha activity during WM retention (Table 1) is similar to what other authors have described Jokisch and Jensen, 2007;Tuladhar et al, 2007). Over time, we found that the maximum alpha power occurred in the middle of the retention interval and diminished towards the end of this period (Fig.…”
Section: Alpha Increase May Reflect Wm Maintenance or Inhibition Of Tsupporting
confidence: 88%
See 1 more Smart Citation
“…For the subjects of the WL+ group, the increase of alpha activity during WM retention (Table 1) is similar to what other authors have described Jokisch and Jensen, 2007;Tuladhar et al, 2007). Over time, we found that the maximum alpha power occurred in the middle of the retention interval and diminished towards the end of this period (Fig.…”
Section: Alpha Increase May Reflect Wm Maintenance or Inhibition Of Tsupporting
confidence: 88%
“…In particular, the role of alpha between WM activity Jokisch and Jensen, 2007;Tuladhar et al, 2007), cortical idling (Pfurtscheller et al, 1996), attention and top-down processes in general von Stein and Sarnthein, 2000) is being discussed (Klimesch et al, 2007;Palva and Palva, 2007). Usually, an increase of alpha power with respect to baseline is called event-related synchronization (alpha ERS) and a decrease event-related desynchronization (alpha ERD).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, gamma power increases are thought to reflect active, neuronal processing, mediating feature binding (e.g. Jokisch & Jensen, 2007). Moreover, it has been proposed that increases in gamma power should be observed when bottom-up information, such as stimulus-related information (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Jokisch & Jensen, 2007). In language comprehension studies, gamma power increases have been associated with semantic unification operations such as the integration of the meaning of an incoming word in a given speech context, access to the mental lexicon (Bastiaansen, Mazaheri & Jensen, 2012), the activation of local functional networks supporting semantic representations (Mellem, Friedman, & Medvedev, 2013) and the predictability of an upcoming word based on the preceding sentence context (Wang, Zhu, & Bastiaansen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is true particularly during rest where thoughts unfold on time scales of several seconds and, thus, require ongoing mnemonic activity, such as retrieval, retention, and manipulation of information (11), to ensure continuity and integrity of conscious experiences (3). Interestingly, working-memory studies have recently associated encoding and retention of information with a sustained increase in the oscillation amplitude for several seconds in multiple brain areas and frequency bands, suggesting that a slow modulation of oscillatory activity is an important systems-level mechanism of mnemonic operations (14)(15)(16). It remains unknown, however, whether amplitude modulation of local oscillatory activity is impaired in a memory disorder like AD and, therefore, could hold valuable diagnostic and prognostic information (4,7).…”
mentioning
confidence: 99%